America in an Arab Mirror: Images of America in Arabic Travel Literature- An Anthology, 1895-1995 by Kamal Abdel-Malek (editor), New York: St. Martin's Press, 2000, 152 pp. (American Journal of Islam and Society, 2001)
How do Arab travelers view the US? Much has been written about how westerntravelers and scholars have seen and described the Orient, thereby not onlycreating an image but also transforming the reality of it. Looking at this anthologyone is reminded of Said's book Orienta/ism and inspired to ask whether asimilar process takes place in reverse. Not in terms of change but certainly increating an image of the unfamiliar as the other simultaneously admired andrejected.Kamal Abdel-Malek has collected and edited texts of twenty-seven Arab visitorsto the United States. Some came as students, others as accomplished scholars orcurious visitors. Each text is an excerpt of a longer text, usually a book, and allbooks were originally published in Arabic and have not been translated intoEnglish before. Also, as Abdel-Malek points out in his preface, the collectionrepresents most of the travel literature he was able to locate in Arabic and iscompleted by a list of all Arabic sources. Thus, this collection allows the readeraccess to a genre of Arabic literature otherwise not available.The travel accounts are organized in five sections and chronologically by year ofpublication within each section.The ftrst section is titled America in the Eyes of a Nineteenth-Century Amb andcontains one account of an Arab traveler to the US published in I 895. The authorpresents the reader with a comparison of what Arabs and Americans findimportant and how these preferences are diametrically opposed in most cases.In the second section Abdel-Malek has gathered a variety of accounts under thetitle The Making of an Image: America as the Unchanged Other, Ame1ica as theSeductive Female. The most interesting piece of this section is probably that ofSayyid Qutb, who studied in the US between 1948 and 1950 and published hisaccount under the title The America I have seen. Much of what he noted about theUS ln the first half of the 20th century, in my opinion, still holds true today. Qutbconcludes: "All that requires mind power and muscle are where American geniusshines, and all that requires spirit and emotion are where American naivete andprimitiveness become apparent .... All this does not mean that Americans are anation devoid of virtue, or else, what would have enabled them to live? Rather, itmeans that America's virtues are the virtues of production and organization, andnot those of human and social morals." (p. 26f.) ...